FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN STRUKTURAL MODAL PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PENGUJIAN PECKING ORDER THEORY - , Andik Susanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Companies in practice require funding either from internal or external funds to finance its operations. Companies also manage its capital structure in order to provide benefits to the company so as to encourage management to manage the capital structure so that the composition of debt or equity can be adjusted with the aim of management in selecting the composition. This study focuses on the pecking order theory by taking a sample of 124 non- financial companies listed on the Indonesia Stock Exchange with the observation year 2009 to 2012 by using 2 models namely the pecking order theory and extended pecking order theory. The purpose of this study is to see if there is consistency of research, as well as the previous studies to answer the research gap of extended pecking order theory model to see the effects of internal funding deficit and the debt ratio to the addition of forming internal funding deficit (dividends payment, additional working capital, investment and net cash flow) for additional debt ratio that can be used as a factor affecting changes in capital structure. The final results in this study support the hypothesis that the entire internal funding deficit has a positive effect on additional debt ratio. Dividend payments, additional working capital and investment have a positive effect while the net cash flow has a negative effect on the addition of the debt ratio. So the company can be said to support the pecking order theory.